Cultural Adaptation of a Text Message Library Designed to Support Diet, Activity and Weight Management Behaviour in the Postpartum Period in the UK: The Supporting MumS (SMS) Study - Eleni Spyreli; Lizzie Caperon; Emma Ansell; Sara Ahern; Sally Bridges; Pat Hoddinott; Michelle McKinley (Proceedings)
The Supporting MumS library of text messages was developed with extensive personal and public involvement (PPI) to help with postpartum weight management and was successfully tested in a feasibility study in Northern Ireland. Before conducting an effectiveness trial, further PPI work was needed to ensure that the dietary and lifestyle advice offered within the SMS text message library was acceptable and culturally relevant for a wide range of women across the United Kingdom (UK). Recruitment was facilitated by existing community networks that helped capture a culturally diverse group of postpartum women who have struggled with their weight. Nineteen women took part in the PPI exercise: n = 4 African–Caribbean (living in London), n = 8 Asian (Bradford), n = 7 white (Scotland). The PPI work followed an iterative process with initial online group discussions, where selected text messages were reviewed and feedback was sought on their language, tone and cultural relevance. This was followed by message adaptation and re-review. Following initial group discussions to understand the main areas for adaptation, PPI work was carried out with individual mums who reviewed the entire library of text messages and provided feedback on all adaptations. Mums liked the humour and the supportive tone of the messages and approximately 15% of the messages were left unchanged. Suggested edits to ensure the messages were acceptable and relevant to women from a range of cultural backgrounds were minor in nature. Suggestions provided by PPI representatives were mainly in relation to broadening the relevance of snack ideas, recipes, food preparation advice, shopping habits (e.g., click and collect services) and workout ideas. Additional feedback included removing colloquialisms and idioms, the meaning of which may be confusing for somebody not familiar with them or a non-native English speaker (e.g., ‘run out of steam’). Personal and Public Involvement provided helpful suggestions for the cultural and regional adaptation of a lifestyle text message intervention in the postpartum period. The effectiveness and cost-effectiveness of the Supporting MumS study will be tested in a UK-wide trial.